New ligation independent cloning vectors for expression of recombinant proteins with a self-cleaving CPD/6xHis-tag. Issue 1 (December 2017) - Biancucci, Marco; Dolores, Jazel; Wong, Jennifer; Grimshaw, Sarah; Anderson, Wayne; Satchell, Karla; Kwon, Keehwan
Abstract Background Recombinant protein purification is a crucial step for biochemistry and structural biology fields. Rapid robust purification methods utilize various peptide or protein tags fused to the target protein for affinity purification using corresponding matrices and to enhance solubility. However, affinity/solubility-tags often need to be removed in order to conduct functional and structural studies, adding complexities to purification protocols. Results In this work, theVibrio cholerae MARTX toxin Cysteine Protease Domain (CPD) was inserted in a ligation-independent cloning (LIC) vector to create a C-terminal 6xHis-tagged inducible autoprocessing enzyme tag, called "the CPD-tag". The pCPD and alternative pCPD/ccdB cloning vectors allow for easy insertion of DNA and expression of the target protein fused to the CPD-tag, which is removed at the end of the purification step by addition of the inexpensive small molecule inositol hexakisphosphate to induce CPD autoprocessing. This process is demonstrated using a small bacterial membrane localization domain and for high yield purification of the eukaryotic small GTPase KRas. Subsequently, pCPD was tested with 40 proteins or sub-domains selected from a high throughput crystallization pipeline. Conclusion pCPD vectors are easily used LIC compatible vectors for expression of recombinant proteins with a C-terminal CPD/6xHis-tag. Although intended only as a strategy for rapid tag removal, this pilot study revealed the CPD-tag may also increase expression and solubility of some recombinant proteins.